25 hill [videorecording (DVD)] - Bernsen, Corbin, 1954-; Gamble, Nathan; Flannigan, Maureen, 1973-; Foster, Meg; Madison, Bailee, 1999-; Tucker, Michael, 1944-; Waite, Ralph, 1928-2014; Heath, Brandon (Echolight Studios, 2011)
"Twelve- year-old Trey Caldwell ... is shattered when his father is killed in Afghanistan, leaving a hole in the boy's life--and an unfinished Soap Box Derby car in the garage. A final gift from his dad, the car is a constant reminder of all that could have been. But when Trey meets Roy Gibbs, a grizzled fire chief devastated by the loss of his firefighter son on 9/11, a new relationship forms and old wounds finally begin to heal"--Container.